China's international development finance: Past, present, and future - Jiajun Xu; Richard Carey (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2015)
China is emerging as perhaps the most globally significant development finance provider, going far beyond concessional foreign aid. With China's initiatives to create and foster new multi-lateral finance institutions, and to work in terms of large economic landscapes in Africa, Eurasia, and Latin America, it becomes important to understand how China's own experience with rapid industrialization/urbanization processes and regional development is influencing its visions and financial instruments for development across the world. This paper examines how China's domestic development experiences have informed its approach to development finance abroad and explores what kinds of challenges and opportunities China will bring as it moves to the centre stage of international development finance.
Keywords: 330; foreign aid; development finance; China